Time-synchronized carbon flow metering scheme for electric power transmission, transformation, and distribution networks - Zhou, Feng; Yu, Jicheng; Yin, Xiaodong; Yue, Changxi; Liang, Siyuan (Frontiers in Energy Research, 2023)
Faced with the pressure of energy conservation and emission reduction, the power industry is urgent for low-carbon transformation. Carbon flow calculation theory redistributes the actual carbon generated by the power plant to the branch and loads customers with the power flow. This paper first introduces the theory of carbon flow calculation and the carbon metrics corresponding to the electricity metrics. Secondly, a time-synchronous technology is introduced for the carbon flow calculation of transmission, transformation, and distribution networks, and a time-synchronous-based carbon metering system is conceived. The impact of time deviation on carbon metering is elucidated through simulation experiments of IEEE14 standard nodes, and finally, relevant suggestions are made for future research ideas and technical routes.